Natural H2 potential in mature volcanic passive margins: A Pelotas Basin overview - Henrique Serratt; Adalene Moreira Silva; Laurent Geoffroy; Tiago Girelli; Matheus Fernandes da Cruz; Peng Peng; Wenbei Shi; Bruno Conti; Marcos Antonio Klunk; Farid Chemale (Journal of South American Earth Sciences, 2026)

Assessing anthropogenic pollution in an oriented nature reserve using Anemonia viridis as a bioindicator - Teresa Bottari; Ilaria Guardamagna; Chiara Anastasia Bruno; Bilal Mghili; Francesca Fabrizi; Caterina Branca; Kannan Gunasekaran; Valeria Conti Nibali; Giovanna D'Angelo; Monique Mancuso (Marine Pollution Bulletin, 2026)

Anthropogenic particles accumulation in sea cucumbers: insights from a transitional environment - Monique Mancuso; Chiara Anastasia Bruno; Ilaria Guardamagna; Bilal Mghili; Francesca Fabrizi; Valeria Conti Nibali; Kannan Gunasekaran; Caterina Branca; Gian Marco Luna; Giovanna D'Angelo; Teresa Bottari (Marine Pollution Bulletin, 2026)

Unraveling the geological history of the South Atlantic margin: Records of West Gondwana Breakup from South Brazil and Uruguay margin - Henrique Serratt; Tiago Jonatan Girelli; Matheus Fernandes da Cruz; Claudia Domingues Teixeira; Ilana Lehn; Monique Aparecida Marchese Rizzi; Marly Babinski; Catarina Laboure Bemfica Toledo; Peng Peng; Bruno Conti; Adalene Moreira Silva; Laurent Geoffroy; et al. (Tectonophysics, 2025)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

Altitudinal variation of microplastic abundance in lakeshore sediments from Italian lakes - Marco Parolini; Elena Perin; Beatrice De Felice; Stefano Gazzotti; Adriano Palazzi; Luca Conti; Eleonora Conterosito; Emanuela Rosio; Francesco Bruno; Valentina Gianotti; Roberto Cavallo (Environmental Science and Pollution Research, 2024)
Microplastic (MP) contamination represents an issue of global concern for both aquatic and terrestrial ecosystems, but only in recent years, the study of MPs has been focused on freshwaters. Several monitoring surveys have detected the presence of a wide array of MPs differing in size, shape, and polymer composition in rivers and lakes worldwide. Because of their role of sink for plastic particles, the abundance of MPs was investigated in waters, and deep and shoreline sediments from diverse lakes, confirming the ubiquity of this contamination. Although diverse factors, including those concerning anthropogenic activities and physical characteristics of lakes, have been supposed to affect MP abundances, very few studies have directly addressed these links. Thus, the aim of the present study was to explore the levels of MP contamination in mountain and subalpine lakes from Northern Italy. Fourteen lakes dislocated at different altitudes and characterized by dissimilar anthropic pressures were visited. Lakeshore sediments were collected close to the drift line to assess MPs contamination. Our results showed the presence of MPs in lakeshore sediments from all the lakes, with a mean (± standard deviation) expressed as MPs/Kg dry sediment accounting to 14.42 ± 13.31 (range 1.57–61.53), while expressed as MPs/m 2 , it was 176.07 ± 172.83 (range 25.00–666.67). The MP abundance measured for Garda Lake was significantly higher compared to all the other ones ( F 1,13 = 7.344; P < 0.001). The pattern of contamination was dominated by fibers in all the lakes, but they were the main contributors in mountain lakes. These findings showed that the MP abundance varied according to the altitude of the lakes, with higher levels measured in subalpine lakes located at low altitudes and surrounded by populated areas.

Heat flow modelling of the Punta del Este Basin (offshore Uruguay) and its correlation with structural crustal domains - Rodrigo Novo; José Alexandre de Jesus Perinotto; Maria Gabriela Castillo; Bruno Conti (Tectonophysics, 2023)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Red list of threatened vascular plants in Italy - Simone Orsenigo; Giuseppe Fenu; Domenico Gargano; Chiara Montagnani; Thomas Abeli; Alessandro Alessandrini; Gianluigi Bacchetta; Fabrizio Bartolucci; Angelino Carta; Miris Castello; Donatella Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Microbiological control and antibacterial action of a propolis-containing mouthwash and control of dental plaque in humans - Karina Basso Santiago; Gilce Maria Piana; Bruno José Conti; Eliza de Oliveira Cardoso; Bruna Fernanda Murbach Teles Andrade; Mirella Rossitto Zanutto; Vera Lúcia Mores Rall; Ary Fernandes; José Maurício Sforcin (Natural Product Research, 2018)

Early effects of exercise training on $$ \mathop V\limits^ · {\rm O}_2 $$ on- and off-kinetics in 50-year-old subjects - Yoshiyuki Fukuoka; Bruno Grassi; Marco Conti; Daniela Guiducci; Monica Sutti; Claudio Marconi; Paolo Cerretelli (Pflügers Archiv - European Journal of Physiology, 2002)